Persepsi Guru dan Peserta Didik Terhadap Penggunaan Blog Berorientasi STEM dengan Strategi Flipped Classroom untuk Meningkatkan Kemampuan Representasi dan Argumentasi: Metode Campuran Cross-Sectional - Nanda Denny DPJ; Dewi Lengkana; Abdurrahman (Jurnal Penelitian Pendidikan IPA, 2023)
The objective of this research was to investigate the Science teachers' and students’ perception toward STEM-Oriented Blogs with the flipped classroom strategy to improve students' representation and argumentation skills. The method used in this research is mixed methods with Sequential Explanatory Design. This research was conducted on 30 junior high school science teachers and involved 76 students of class VII junior high school. Data were obtained through questionnaires distributed online and interviews online via WhatsApp video calls, then analyzed using descriptive analysis. The result shows that teachers and students have a positive perception toward STEM-Oriented Blogs with the flipped classroom strategy. As 80% of teachers had not used blog as learning media; all of students needs learning media that can be accessed via smartphones. The current media learning has not completely train students' representation and argumentation skills and that's skills was in low category. Based on the result, it can be concluded that STEM-Oriented Blogs with the flipped classroom strategy is needed to improve students' representation and argumentation skills.